Ethnic peculiarities of ischemic heart disease prevalence rate for Yakutia urban population aged 60 years and over - O. V. Tatarinova; Yu. P. Nikitin; V. N. Neustroeva; L. V. Shcherbakova (Атеросклероз, 2013)
Subject to population screening study the ethnic peculiarities of prevalence rate of ischemic heart disease and its basic risk factors for inhabitants of Yakutia aged 60 years and over were studied as well as the contribution of some risk factors to development of IHD at people of old age residing within the conditions of Extreme North. Epidemiological methods helped to reveal high IHD prevalence rate at Yakut and Caucasian old age population residing in the Republic of Sakha Yakutia (40 and 47 % respectively, р = 0.09) and its risk factors. At advanced-age groups (for Yakut population – 90 years and older, for Caucasians – 80 years and older) the IHD occurs oftener than at the inhabitants of Yakutia aged 60–70 years. Among aged representatives of Yakut nationality compared with people of old age of Caucasian ethnic affiliation the more favourable profile of IHD risk factors was diagnosed. The significant contribution into IHD development at Yakut population is made by HDL hypocholesterolemia and obesity, and at Caucasian – C-creative protein, pulse pressure and obesity.